Successful Management of Esophageal Atresia with Tracheoesophageal Fistula in a 7-Day-Old Male Infant - Rizky Ardiansyah Sipayung; Thomas Aribowo Kristianto; Suwardi (Open Access Indonesian Journal of Medical Reviews, 2025)
Esophageal atresia (EA) with tracheoesophageal fistula (TEF) is a rare congenital anomaly characterized by an incomplete esophagus and an abnormal connection between the trachea and esophagus. This condition occurs in approximately 1 in 3000 to 5000 live births and requires prompt diagnosis and surgical intervention to prevent life-threatening complications. The most common type of EA with TEF involves a proximal esophageal atresia and a distal TEF (Type C). Early diagnosis is crucial to prevent complications such as aspiration pneumonia. Surgical repair is the definitive treatment for EA with TEF, and the surgical approach involves thoracotomy, fistula ligation, and end-to-end esophageal anastomosis. This report describes the case of a 7-day-old male infant who presented with respiratory distress, excessive oral secretions, and an inability to pass a nasogastric tube. Radiographic imaging confirmed the diagnosis of EA with TEF Type C. The infant underwent successful surgical repair, including thoracotomy, fistula ligation, and end-to-end esophageal anastomosis. The postoperative course was complicated by minor wound dehiscence, which healed with secondary intention. The infant was discharged on the 10th postoperative day with no further complications. In conclusion, This case highlights the importance of a multidisciplinary approach involving neonatologists, pediatric surgeons, anesthesiologists, and nurses in the successful management of EA with TEF. Early diagnosis, prompt surgical intervention, and comprehensive postoperative care are essential for achieving favorable outcomes in infants with this condition. With appropriate management, most infants with EA with TEF can achieve normal growth and development.